Pengaruh Pemanfaatan Dana Corporate Social Responsibility Bidang Lingkungan Terhadap Penyaluran Dana Dan Perlindungan Lingkungan Hidup Di Kabupaten Bengkalis - Muhammad Fadhil Junery; Dedi Setiawan (JAS (Jurnal Akuntansi Syariah), 2019)
This research was conducted to determine the effect of the use of Corporate Social Responsibility funds in the environmental sector on the distribution of funds and environmental protection in Bengkalis Regency. In this study, researchers used Corporate Social Responsibility fund report data recorded in the Department of Environment of Bengkalis Regency in the period of 2016 to 2018. The test results show that Corporate Social Responsibility funds in the environmental field have a significant positive effect on efforts to protect and manage the environment in Bengkalis Regency with an R Square value of 0.804. This shows that the percentage of the influence of the use of CSR funds in the environmental sector has a significant positive effect on environmental protection and management efforts in Bengkalis Regency by 80.4%, while the remaining 19.6% is influenced by other variables outside this research.